Early loop ileostomy closure: should we do it routinely? - Viktorija Žukauskienė; Narimantas Evaldas Samalavičius (Lietuvos Chirurgija, 2013)
Background / objective Temporary loop ileostomies are usually performed in colorectal surgery after colectomies with ileoanal or coloanal or low colorectal anastomosis to prevent life-threatening complications associated with anastomotic leakage. However, stoma itself is not without adverse events. They are usually closed at 8 to 12 week, or sometimes even later after full course of adjuvant chemotherapy. The aim of this study was to review our experience with early loop ileostomy closure, during same hospitalization as initial surgery. Patients / methods Complications and postoperative morbidity after early loop ileostomy closure were assessed retrospectively by reviewing the medical records. Out of the 12 patients, 6 were male and 6 – female, on an average 66 years old (range 29 to 85 years). Ileostomy was performed due to following reasons: 9 patients with rectal cancer after total mesorectal excision, one patient after low colorectal anastomosis due progression of ovarian cancer, one patient after resection of anastomosis and coloanal anastomosis due to stricture after previous partial TME for upper rectal cancer, one after coloanal anastomosis due to Hartman’s reversal procedure for previous rectal cancer. Anastomotic integrity was examined using proctography with water-soluble contrast before closure in all patients. The average time after initial surgery to loop ileostomy closure was 11 days. Results There was no mortality. Overall complication rate was 33 percent (4 patients). One patient (8,3%) had a bowel obstruction, which resolved after conservative treatment. One patient (8.3%) developed enteric fistula to the ileostomy incision and wound infection was noted in two (16.6%). Conclusions Despite of the fact that small number of patients was analyzed - high overall complication rate was observed. Nevertheless all complications were managed conservatively without reoperation. Early stoma closure is feasible in selected patients without anastomotic complications. Key words: colorectal resection, colorectal cancer, loop ileostomy, early closure.